The redemption of Morgan Bright - Panatier, Chris (Angry Robot, and imprint of Watkins Media Limited, 2024)
What would guilt make you do? Hadleigh Keene died on the road leading away from Hollyhock Asylum. The reasons are unknown. Her sister Morgan blames herself. A year later with the case still unsolved, Morgan creates a false identity, that of a troubled housewife named Charlotte Turner, and goes inside. Morgan quickly discovers that Hollyhock is... not right. She is shaken by the hospital's peculiar routines and is soon beset by strange episodes. All the while, the persona of Charlotte takes on a life of its own, becoming stronger with each passing day. As her identity begins unraveling, Morgan finds herself tracing Hadleigh's footsteps only to discover the dark secrets of Hollyhock and how deeply they are buried...